2023
DOI: 10.1038/s43587-023-00431-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeting lymphoid-derived IL-17 signaling to delay skin aging

Abstract: Skin aging is characterized by structural and functional changes that contribute to age-associated frailty. This probably depends on synergy between alterations in the local niche and stem cell-intrinsic changes, underscored by proinflammatory microenvironments that drive pleotropic changes. The nature of these age-associated inflammatory cues, or how they affect tissue aging, is unknown. Based on single-cell RNA sequencing of the dermal compartment of mouse skin, we show a skew towards an IL-17-expressing phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 89 publications
0
8
0
1
Order By: Relevance
“…Previous studies have reported that senescent cells delay healing in old individuals, such as fracture healing 29,30 . In ageing skin, senescent fibroblast accumulation and a local environment resembling a low‐level but persistent chronic inflammatory state could be the contributors to delayed wound healing 31 . To determine whether there is a correlation between senescence cells and healing delay induced by SPESP1 knockdown, we repeated the D+Q experiment in shNC and shSpesp1 wounded mice and assessed SPESP1, DCN and senescence markers (p53 and p21) expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that senescent cells delay healing in old individuals, such as fracture healing 29,30 . In ageing skin, senescent fibroblast accumulation and a local environment resembling a low‐level but persistent chronic inflammatory state could be the contributors to delayed wound healing 31 . To determine whether there is a correlation between senescence cells and healing delay induced by SPESP1 knockdown, we repeated the D+Q experiment in shNC and shSpesp1 wounded mice and assessed SPESP1, DCN and senescence markers (p53 and p21) expression.…”
Section: Resultsmentioning
confidence: 99%
“… 29 , 30 In ageing skin, senescent fibroblast accumulation and a local environment resembling a low‐level but persistent chronic inflammatory state could be the contributors to delayed wound healing. 31 To determine whether there is a correlation between senescence cells and healing delay induced by SPESP1 knockdown, we repeated the D+Q experiment in shNC and shSpesp1 wounded mice and assessed SPESP1, DCN and senescence markers (p53 and p21) expression. The protein expression of both SPESP1 and DCN was remarkably reduced in the traumatized tissues of shSpesp1 mice, but both were reversed after D+Q treatment (Figure 7A and Supplementary Figure 10A ).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the pathway activation of NF-kappa B has a causal role in promoting senescence, and the association of them have response to chemotherapy ( 33 , 34 ). Through NF-kappa B in epidermal cells, aberrant IL-17 signaling during ageing impairs homeostatic functions, and promotes an inflammatory state ( 35 ). The functional annotations of the biological process GO also demonstrated that each cell had a distinct role in the development of diseases.…”
Section: Resultsmentioning
confidence: 99%
“…T17s displayed different intergroup spatial position to the ECM scaffold. T17s in Young_ECM are mostly distributed in the fibroblastrich granulation tissue below the ECM scaffold to enhance fibroblast migration and collagen deposition 50,51 , while located on the wound margin around scaffolds in Aged_ECM, where the secretion of IL-17 was proven to exacerbate local inflammation 52,53 , in line with the poor reepithelialization (Extended Data. Fig 5. f).…”
Section: Resultsmentioning
confidence: 99%